Pushing past the human in Latin American cinema - Fornoff, Carolyn; Heffes, Gisela, 1971- (Albany : State University of New York Press, 2021)
"Sheds light on emergent Latin America cinema that addresses the politics of environmental destruction, the uneveness of climate change consequences, and new ways of visualizing the world beyond the human"--
Introduction: Latin American Cinema Beyond the Human / Carolyn Fornoff and Gisela Heffes -- Part 1: Genre Beyond the Human : 1. Movies on the Move: Filming the Amazon Rainforest / Patrícia Vieira -- 2. Visualizing the Geosphere: The 1985 Earthquake in Mexican Cinema / Carolyn Fornoff -- 3. Revisiting Nature and Documenting the Americas: From Alexander von Humboldt to the Contemporary Latin American Documentary / Juana New -- 4. Slow Violence in the Slow Cinema of Lisandro Alonso / Amanda Eaton McMenamin -- Part 2: Encountering Difference : 5. Humanimal Assemblages: Slaughters in Latin American Left-Wing Cinema / Moira Fradinger -- 6. Reordering Material Hierarchies in Jossie Malis Álvarez's Animated Series, Bendito Machine Katherine Bundy -- 7. Mapping Queer Natures in Papu Curotto's Esteros / Vinodh Venkatesh -- 8. Counterflows: Hydraulic Order and Residual Ecologies in Caribbean Fantasy Landscapes / Lisa Blackmore -- 9. Differential Viscosities: The Material Hermeneutics of Blood, Oil, and Water in Crude and The Blood of Kouan Kouan / Mark Anderson -- Part 3: Screening the Pluriverse : 10. Human Rights at the End of the World: Patricio Guzmán and the "Imperative to Reimagine the Planet" / Fernando J. Rosenberg -- 11. Sea Turtles and Seascapes: Representing Human-Nature Relations in the Central American Caribbean / Mauricio Espinoza and Tomás Emilio Arce -- 12. Refracting Lenses on the Atlantic Coast of Nicaragua: Documenting Social Ecologies and Biospheres in El ojo del tiburón and El canto de Bosawas / Julia M. Medina -- 13. The Sacred Space of Motoapohua: Intercorporeal Animality and National Subjectivities in Nicolás Echevarría's Eco de la montaña / Iván Eusebio Aguirre Darancou -- 14. Undisciplined Knowledge: Indigenous Activism and Decapitation Resistance / Gisela Heffes.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Motion pictures -- Latin America -- History; Climatic changes in motion pictures; Ecology in motion pictures; Cinéma -- Amérique latine -- Histoire; Climat -- Changements, au cinéma.; PERFORMING ARTS / Film & Video / History & Criticism; Climatic changes in motion pictures; Ecology in motion pictures; Motion pictures; Latin America; History